The view from the ground : experiences of Civil War soldiers - Sheehan-Dean, Aaron Charles (New directions in southern history., 2007)
With an Afterword by Joseph T. Glatthaar The View from the Ground brings together the perspectives of Civil War soldiers on all aspects of the conflict, revealing as much about nineteenth-century America as it does about the war itself. The contributors investigate the issues engaged by soldiers during the war, including slavery and racial tensions, the isolation that many men of faith felt in the early months of the war, the divide between soldiers and civilians, and the inherent difficulty in reconciling the act of killing with Christian precepts of charity and peacefulness. They also explor.